Unequal Opportunity, Unequal Growth - Marrero, Gustavo A.; Rodriguez, Juan Gabriel; van der Weide, Roy (World Bank, Washington, DC, 2016)
This paper argues that inequality can be both good and bad for growth, depending on what inequality and whose growth. Unequal societies may be holding back one segment of the population while helping another. Similarly, high levels of income inequality may be due to a variety of different factors; some of these may be good while others may be bad for growth. The paper tests this hypothesis by “unpacking” both inequality and growth. Total inequality is decomposed into inequality of opportunity, due to observed factors that are beyond the individual's control, and residual inequality. Growth is measured at different steps of the income ladder to verify whether low, middle, and top income households fare differently in societies with high (low) levels of inequality. In an application to the United States covering 1960 to 2010, the paper finds that inequality of opportunity is particularly bad for growth of the poor. When inequality of opportunity is controlled for, the importance of total income inequality is dramatically reduced. These results are robust to different measures of inequality of opportunity and econometric methods.